Answer:
Step-by-step explanation:
To find the solutions for the equation (3m - 7)(3m + 6) = 0, we can set each factor equal to zero and solve for m.
Setting the first factor, 3m - 7, equal to zero:
3m - 7 = 0
Adding 7 to both sides:
3m = 7
Dividing both sides by 3:
m = 7/3
Setting the second factor, 3m + 6, equal to zero:
3m + 6 = 0
Subtracting 6 from both sides:
3m = -6
Dividing both sides by 3:
m = -6/3
Simplifying:
m = -2
Therefore, the solutions for the equation (3m - 7)(3m + 6) = 0 are m = -2 and m = 7/3.
So, the correct answer is A. {-2, 7/3}.